Evolution of the institutional capacity of the São Paulo Metropolitan Region in relation to climate change - Queiroz, Leonardo Rossatto; Marchezini, Victor; Rodriguez, Daniel Andres (Cadernos Metrópole, 2023)
This article proposes a methodology of analysis of the institutional capabilities that are employed to cope with climate change at the municipal and metropolitan levels. The methodology was applied to the São Paulo Metropolitan Region using Environmental and Disaster Risk Management data, collected by the Brazilian Institute of Geography and Statistics (IBGE) through the National Survey of Municipal Information (MUNIC), years 2013, 2017, and 2020. The results indicate that municipal institutions consistently lost capabilities to cope with climate change between 2013 and 2020. There is a considerable difference in the pattern of this loss when the analysis focuses separately on institutional capacity to deal with environmental management and with disaster risk management.